Strategi Inovasi Pengembangan SDM Aparatur di Era Digitalisasi BPSDMD Provinsi Banten - Gimas Rahadyan; Jeni Minan; Rizka Maulidina Sumita (ijd-demos, 2025)
Local governments are required to adapt to electronic systems through the Electronic-Based Government System (SPBE) policy. The Human Resources Development Agency (BPSDMD) of Banten Province faces challenges regarding low digital literacy among civil servants, a conventional work culture, and limited network infrastructure. This study aims to assess the effectiveness of innovation strategies for civil servant human resource development in addressing these challenges, utilizing Chandler’s strategy theory and Bekkers’ digitalization framework. A descriptive qualitative approach was employed, involving interviews, observations, and document analysis. The results indicate that BPSDMD Banten Province successfully implemented blended learning and remote learning methods, alongside optimizing the "Banten Ceria" and "Teko Banten" Learning Management Systems (LMS). Key supporting factors included central policy support, physical facilities, and regional budget (APBD) allocations; conversely, network disruptions and participants' limited digital literacy acted as obstacles, which were mitigated through a humanistic support approach and the simplification of application interfaces. It is concluded that digitalization innovation strategies are crucial for bureaucratic transformation; however, they require continuous post-training performance evaluation and the enrichment of interactive features to maximize employee competence in public service. The study recommends that the agency strengthen internet infrastructure redundancy, recruit additional programming experts, and expand micro-learning content to ensure the innovation remains responsive to technological advancements. Keywords: Strategy; Innovation; Human Resource Development; Civil Servants; Digitalization